Dinâmica evolutiva dos clusters de pequenos RNAs nucleares (RNAsn) nos cariótipos de espécies de gafanhotos com ênfase em Acrididae - Anjos, Allison Kleiton dos [UNESP] (2014)
The spliceosome is responsible for mRNA maturation through intron removal. This machinery is formed by a protein set associated to small nuclear RNA (snRNA). Among the snRNA genes, the U1 snRNA is, in general, a conserved 165 bp tandemly arrayed repetitive sequence. Aiming to contribute to the understanding of chromosome and genome dynamics of multigene families in grasshoppers we mapped the U1 snRNA genes by Fluorescent in situ Hybridization (FISH) in 71 grasshopper species belonging to the families Proscopiidae, Pyrgomorphidae, Ommexechidae, Romaleidae and Acrididae. Moreover we analyzed the genomic organization for this sequence using as reference the sequenced genome through 454 of Eyprepocnemis plorans. High conservation of snDNA clusters mainly located on autosome pairs (no. 3 or 4) was observed in the first four families. In contrast, extensive variation was observed in Acrididae species, from a single chromosome pair carrying U1 snDNA to all chromosome pairs carrying them, with occurrence of two or multiple clusters in the same chromosomes. In the genome of E. plorans five distinct lineages were observed with distinct patterns of variability and association of U1 snDNA with transposable elements and 5S rDNA was also noticed. These results are discussed focusing the possible mechanisms of spread of this gene cluster, which apparently seems to have followed different ways of dispersion in the several families and subfamilies analyzed in here. This is the most comprehensive study on FISH mapping hitherto performed in grasshoppers and other organisms by studying 71 species from five families and has thus provided valuable information shedding light in the chromosomal/genomic evolution of this gene family by combined use of chromosomal and genomic data